ANALISIS PERGERAKAN RUPIAH DI PASAR UANG TERHADAP KINERJA KEUANGAN (RETURN ON ASSET DAN RETURN ON EQUITY) PT INDOFOOD SUKSES MAKMUR, TBK (TRIWULANAN) DARI TAHUN 2010-2016 - Mario Adventino Hamboerh; Siti Saadah (Prosiding Working Papers Series In Management, 2017)
Multinational Companies always make sell and purchase transactions using foreign currency that has been agreed before. Stability foreign currency in transaction is what company expectations. Financial performance is one things can be affected because of the change in value of foreign currency. Return on Asset is a ratio looking at the company profit with total asset owned by the company. Return on Equity is a ratio looking the company profit with total equity / company’s capital in operational activities.One of the multinational company and located in Indonesia is PT Indofood Sukses Makmur, Tbk. This research aims to analyze the impact of exchange rate changes on financial performance of PT Indofood Sukses Makmur, Tbk. The method in this research with Error Correction Model (ECM) and uses time series data in E-views 9.0 software. Data obtained from www.bi.go.id, www.indofood.com, www.sahamok.com The result of this research with significant level ( = 5%), show that there is no significant on the exchange rate variable to Return on Asset (ROA) and Return on Equity (ROE) in 2010-2016. Finally, ROA and ROE PT Indofood Sukses Makmur, Tbk is not influenced by exchange rate movements.Keywords: Foreign Currency, Return on Asset, Return on Equity